Study Habits and Learning Styles as Predictors of Academic Achievement of Secondary School Students in Anambra State (Journal of Guidance and Counselling Studies, 2024)
This study investigated study habits and learning styles as predictors of academic achievement of secondary school students in Anambra state. The study adopted the correlation survey design of the predictive nature. Three research questions guided the study, while three hypotheses were tested at 0.05 alpha level. The population for this study comprises 18,787 Senior Secondary School two SS II students from 261 secondary schools situated in the six education zones in Anambra state.Multi-stage sampling procedure was used to select a sample size of 825 SS II students from the six education zones in Anambra state. The instruments adopted for data collection were standardized Study Habit Scale (SHS) developed by Bakare (1977) and the Learning Style Inventory developed by Daid Kolb (1971). These instruments were administered using direct delivery approach with the help of six classroom teachers in the sampled schools who doubled as research assistants. Research questions were answered using multiple regression analysis to determine the R, R-square and R2 adjusted.The academic achievement scores collected for the undergraduates which comprise of scores and grades in English language indicating their achievements. The findings from the study revealed among others that a there is a low positive linear relationship between secondary school students’ study habit and their academic achievement in English Language in Anambra State. A low positive linear relationship exists among secondary school students study habits and learning styles on their academic achievement in English language in Anambra state.Conclusions were made, and it was recommended that school teachers and principals should re-organize and integrate students in study groups and JET clubs so as to improve their study habit and learning styles. More so, the home background and the peers they interact with also matters. This will help reshape their perception of their immediate environment.
Keywords: Study habit; Learning styles; Academic Achievement; Secondary Schools; Students